2014
DOI: 10.3109/00365513.2014.905697
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise in elite rugby players increases the circulating level of the cardiovascular biomarker GDF-15

Abstract: The measure of GDF-15 in professional rugby players could be a useful tool to monitoring their cardiovascular status during training and competition session in order to prevent the onset of collateral cardiovascular adverse event due to the intense training and, in the case of cardiac injury, it could possibly allow a very early diagnosis at the beginning of the pathogenic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
3
24
0
1
Order By: Relevance
“…These results indicate that biochemical changes do exist in serum after a training session, as shown in other studies (Déléris and Petibois, 2003;Galliera et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…These results indicate that biochemical changes do exist in serum after a training session, as shown in other studies (Déléris and Petibois, 2003;Galliera et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…GDF-15 is accepted as an independent prognostic factor in predicting CVD and adverse outcome, over and above clinical and biochemical markers including troponins and natriuretic peptides (3). However, to the best of our knowledge no study to date has investigated the resting plasma GDF-15 levels in athletes, especially in the adolescents.…”
Section: Discussionmentioning
confidence: 92%
“…In the previous studies (3,16,17) it has been demonstrated that both intense physical activity such as marathon running (8) or soccer match (16) and exercise training (3) increased GDF-15 levels in elite athletes. On the other hand, Munk et al (25) showed that moderate exercise training (i.e., 3 times a week, for 1 hour, over 6 months) did not affect plasma GDF-15 levels in patients with stable coronary artery disease.…”
Section: Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated serum levels of GDF-15 were also observed within one hour of exercise. In this regard, it can be stated that GDF-15 may increase in response to stress and cellular damage caused by acute exercise, which may continue for several hours after exercise [12].…”
Section: Resultsmentioning
confidence: 99%